Impacto de intervenção nutricional, pautada no modelo transteórico para controle de peso, na atenção primária: ensaio clínico controlado randomizado - Patricia Pinheiro de Freitas (2015)
The high prevalence of excess weight and its consequences demand effective actions, especially in primary health care. Objective: To assess the effectiveness of individual nutritional follow-up based on the transtheoretical model to control weight in overweight women frequenting a unit of the Program Academia da Saúde of Belo Horizonte, Minas Gerais, according to parameters of food intake, anthropometric and biochemical. Methods: This is a randomized controlled clinical trial with overweight women aged 20 or more years who frequent a unit of the Program Academia da Saúde. The women in the Control Group (CG) and Intervention Group (IG) participated in the routine activities provided by the service (physical exercise and group actions related to food and nutrition education). Additionally, those in the IG received individual nutritional counseling based on the transtheoretical model for six months. Their socioeconomic, health, eating and anthropometric profile were determined at baseline and end of study and a random subsample (40%) was submitted to metabolic and inflammatory marker assessments (total cholesterol and fractions, triglycerides, fasting glucose, plasma insulin, adiponectin, resistin, IL-6, IL-10, and TNF-). Intragroup (paired Students t-test, McNemar, and Wilcoxon tests) and intergroup (Students t-test, Mann-Whitney, chi-square, and Fishers exact tests) statistical analyses were performed. The effectiveness of the intervention was verified by analysis of covariance (ANCOVA) for the outcomes weight, body mass index (BMI), waist circumference (WC), and serum levels of resistin and adiponectin adjusted for age and baseline values (p<0.05). Results: Eighty-six women were assessed, 35 in the CG and 51 in the IG. After a six-month follow-up, 33.3% of the IG and 31.4% of the CG had dropped out (p=0,853). The participants in the IG increased the number of daily meals (p=0.030); reduced their availability daily per capita sugar intake (p=0.004); reached the final stages of change for controlling servings (p=0.016); reduced saturated (p<0.001) and polyunsaturated (p<0.001) fatty acid intakes; reduced WC (p=0.019); and had lower serum glucose levels (p=0.006). The participants in the CG reduced the number of daily meals (p<0.001) and increased their saturated fatty acid intake (p<0.001). Was found lower mean weight (p=0.013) and BMI (p=0.038) in IG participants compared with the CG. Conclusion: The nutritional intervention based on the transtheoretical model for weight loss effectively reduced body weight and improved the health and nutrition profile of the participants. These results show the importance of carrying out specific interventions in primary health care for controlling the weight of overweight women with comorbidities, considering whether the women are ready to change and to learn to make healthy food choices autonomously.